2004
DOI: 10.1002/jmri.20031
|View full text |Cite
|
Sign up to set email alerts
|

MRI of bone tumors: Fast STIR imaging as a substitute for T1‐weighted contrast‐enhanced fat‐suppressed spin‐echo imaging

Abstract: Purpose:To compare the usefulness of short inversion recovery (STIR) and T1-weighted, contrast-enhanced, fatsuppressed (T1W-CEFS) sequences for the evaluation of bone tumors. Materials and Methods:Eighteen patients with 19 bone tumors who underwent both STIR and T1W-CEFS imaging were evaluated. The tumors were categorized in pairs as follows: bone marrow and soft-tissue components, benign and malignant tumors, and tumors with and without mineralization. The signal difference-to-noise ratio (SDNR), signal-to-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
1
9
0
3
Order By: Relevance
“…However, advances in MR technology as well as improved soft tissue contrast and anatomical resolution on high field MR scanners give rise to the question if the administration of contrast agents is actually always needed. Tokuda and colleagues recently reported comparable results for differentiation of benign from malignant tumors in soft tissue masses (17) and even better results for differentiation of benign from malignant bone tumors by using fast short tau inversion recover (STIR) imaging (18) suggesting that contrast enhancement is not always needed. In addition diffusion weighted MR imaging provides information about solid and cystic/necrotic tumor areas, which was previously only accessible with contrast-enhanced sequences (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, advances in MR technology as well as improved soft tissue contrast and anatomical resolution on high field MR scanners give rise to the question if the administration of contrast agents is actually always needed. Tokuda and colleagues recently reported comparable results for differentiation of benign from malignant tumors in soft tissue masses (17) and even better results for differentiation of benign from malignant bone tumors by using fast short tau inversion recover (STIR) imaging (18) suggesting that contrast enhancement is not always needed. In addition diffusion weighted MR imaging provides information about solid and cystic/necrotic tumor areas, which was previously only accessible with contrast-enhanced sequences (19).…”
Section: Discussionmentioning
confidence: 99%
“…Gd-DTPA shortens the T1 relaxation time in tumors, causing an increase in signal intensity in vascular regions versus necrotic regions and normal tissue [39]. However, Gd-DTPA is not routinely used for imaging of bone metastases and due to the additional scan time required, was not included in this study.…”
Section: T2 Mr Imaging Demonstrates Tumor Associated Bone Destructionmentioning
confidence: 91%
“…PET is therefore considered superior to bone scintigraphy for the detection of bone metastases. Currently, MR imaging with the use of various sequences such as T1-weighted SE or turbo SE imaging, T2-weighted turbo SE imaging, STIR turbo SE imaging, contrastenhanced T1-weighted SE or turbo SE imaging, or diffusion-weighted MR imaging is deemed useful for assessment of muscle-skeletal tumors and metastasis from various malignancies (Weinberger et al 1995;Vanel et al 1998;Mentzel et al 2004;Park et al 2004;Tokuda et al 2004;Goo et al 2005). However, only one study has directly compared the diagnostic capability of MR imaging and bone scintigraphy and found that sensitivity, specificity and accuracy of MR imaging were 80%, 96% and 93%, respectively, being superior to bone scintigraphy (40%, 92%, and 83%), although the difference was not significant (Earnest et al 1999).…”
Section: Bone Metastasismentioning
confidence: 99%